2013
DOI: 10.3174/ajnr.a3704
|View full text |Cite
|
Sign up to set email alerts
|

Long Insular Artery Infarction: Characteristics of a Previously Unrecognized Entity

Abstract: BACKGROUND AND PURPOSE:The infarctions arising in the long insular arteries of the M2 segment have been poorly described in the past. The purpose of this study was to investigate the incidence, clinical characteristics, and pathogenesis of long insular artery infarcts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Preservation of the long insular artery to prevent postoperative motor deficits (insular cortex lesion) needs knowledge of normal and variable branching pattern of M2 segment . 16,17 However the comparision of lengths of middle cerebral artery trunks and their reference with insula discussed, which can be of great clinical significance.…”
Section: Observation and Resultsmentioning
confidence: 99%
“…Preservation of the long insular artery to prevent postoperative motor deficits (insular cortex lesion) needs knowledge of normal and variable branching pattern of M2 segment . 16,17 However the comparision of lengths of middle cerebral artery trunks and their reference with insula discussed, which can be of great clinical significance.…”
Section: Observation and Resultsmentioning
confidence: 99%
“…[1][2][3] Among the deep penetrating arteries, the lenticulostriate arteries (LSAs) are branches of M1 segment of the MCA and supply the lower part of the corona radiata. 1,4,5 The superficial penetrating arteries, known as the white matter medullary arteries (WMMAs) and originating from the cortical branches of the MCA, supply the periventricular deep white fiber tract. [1][2][3] LIA is a unique artery that supplies the periventricular white matter.…”
Section: Discussionmentioning
confidence: 99%
“…The LIA infarction has been identified principally by neurosurgeons as interruption of this artery during the resection of opercular glioma often ended in postoperative hemiplegia/hemiparesis and classical corona radiata infarction. 1,[4][5][6] The LIA arises from the M2-upper trunk in the upper insular cleft and supplies the insular cortex, extreme capsule, claustrum, and external capsule and quite often extends to the corona radiata (►Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these authors, in the transsylvian route, the risk of vascular injury and pial transgression during the course of exposure is not insignificant. Concerning strokes, Tamura et al, in a retrospective study of 356 patients suffering from acute ischemic stroke, report 8 cases of long IPA infarcts well documented by MRI [11]. For these authors, long IPA infarctions were found to be more common than previously thought and possessed clinical characteristics of classic lacunar syndrome, which often consists of pure motor strokes.…”
mentioning
confidence: 99%